One-step separation of myristoylated and nonmyristoylated retroviral matrix proteins - Doležal, Michal; Zábranský, Aleš; Hrabal, Richard; Ruml, Tomáš; Pichová, Iva; Rumlová, Michaela (Protein expression and purification, 2013)
N-terminal myristoylation of retroviral matrix proteins is essential for the targeting of the Gag polyproteins to the plasma membrane. To investigate the effect of the myristoylation on the structure and membrane binding ability of the matrix proteins, it is necessary to prepare their myristoylated forms. We present purification of myristoylated matrix proteins of the mouse mammary tumor virus and murine leukemia virus, two morphogenetically distinct retroviruses. The proteins were expressed in Escherichia coli coexpressing a yeast N-myristoyltransferase. This E. coli expression system yielded a mixture of myristoylated and nonmyristoylated matrix proteins. We established efficient one-step metal affinity purification that enabled to obtain pure myristoylated matrix proteins suitable for structural and functional studies.
Keywords: virus myší leukemie; nukleární magnetická rezonance biomolekulární; Cloning, Molecular; Retroviridae - proteiny; Mice; zvířata; Leukemia Virus, Murine; Nuclear Magnetic Resonance, Biomolecular; chromatografie afinitní; Retroviridae Infections; kyselina myristová; Chromatography, Affinity; rekombinantní proteiny; Myristic Acid; myši; Recombinant Proteins; Animals; klonování DNA; retrovirové infekce; Retroviridae Proteins